Why we should be looking for longitudinal patterns in biodiversity - Procheş, Şerban; Watkeys, Michael K.; Ramsay, Lisa F.; Cowling, Richard M. (Frontiers in Ecology and Evolution, 2023)
Our understanding of global diversity patterns relies overwhelmingly on ecological and evolutionary correlates of latitude, and largely ignores longitude. However, the two major explanations of biodiversity patterns – energy and stability – are confounded across latitudes, and longitude offers potential solutions. Recent literature shows that the global biogeography of the Cenozoic world is structured by longitudinal barriers. In a few well-studied regions such as South Africa’s Cape, the Himalayas and the Amazon-Andes continuum, there are strong longitudinal gradients in biodiversity. Often, such gradients occur where high and low past climatic velocities are juxtaposed, and there is clear evidence of higher biodiversity at the climatically-stable end. Understanding longitudinal biodiversity variations more widely can offer new insights towards biodiversity conservation in the face of anthropogenic climatic change.